Pengaruh Jenis Umbi Gadung (Dioscorea hispidaDennst.) Terhadap Kadar Bioetanol pada Proses Fermentasi Menggunakan Ragi Roti - Puri Handayani; Khaidir Khaidir; Zurrahmi Wirda (Faculty of Agriculture, Universitas Malikussaleh, 2017)
The objective of this research is to reveal the influence of the type of gadung to the produced ethanol content, the yeast concentration which is suitable to get the maximum ethanol and to know the interaction between the type of gadung and the yeast concentration on the ethanol content produced. The research using Randomized Complete Design with factorial pattern consisted of 2 factors: the gadung bulb type (U), as the first factor consisting of white gadung tuber (U1) and yellow bulb tuber (U2) second factor yeast concentration consisting of 2 , 5% (R1), 3% (R2), 3.5% (R3). Fermentation duration is done for 3 days. Each treatment is repeated 3 times. The results showed that the proximate analysis on two types of gadung is highest in white gadung. The average width of the highest gadung leaves on white gadung . Test brix on the highest gadung tubers on white gadung. On observation of the highest yield of ethanol occurs on the type of white gadung and 2.5% yeast concentration. The best type of mass observation occurred in yellow gadung tuber type and 2.5% yeast concentration. Observation of initial pH of ethanol was highest in white gadung and yeast concentration 2.5%. Observation of pH after distillation is highest on white gadung and at yeast concentration 2.5%. The highest concentration of ethanol content on yellow gadung and at yeast consentation 2.5%. The observation of the highest ash content on yellow gadung and at yeast concentration 3.5%.